CONSTRUCTING ECOLOGICAL MEANING IN CORPORATE SUSTAINABILITY REPORTING: A CRITICAL ECOLINGUISTICS ANALYSIS OF SINAR MAS LAND - Muhammad Munawir; Junaidi (Lire Journal (Journal of Linguistics and Literature), 2026)
This study analyses the use of ecological meanings in Sinarmas Land's Sustainability Reports (2017–2024), a prominent Indonesian homebuilder. The study employs Arran Stibbe's "Stories We Live By" and Norman Fairclough's Critical Discourse Analysis methodology. This study employs USAS for corpus-assisted semantic analysis. Semantic tagging helped us find 157 important words in the areas of World and Environment (W), Social Actions and Processes (S), and Government and Public (G). The study shows that three related trends have an effect on environmental discourse. Sustainability is a part of G because of rules that are in line with each other, certification, and compliance frameworks. This gives the government the power to control ecological sustainability. The corporation is an ethical environmental player in the S domain because stories about stewardship, awareness, and community empowerment make environmental duties moral and shared. The last area recognises ecological elements and processes, although they are slowly added to resource optimisation and technologically scientific management. This brings together protecting the environment with new ideas and growth. The results indicate that corporate sustainability discourse constitutes neoliberal environmental governance. This kind of government combines concern for the environment with growth.